I don’t feel no ways tired: a black woman’s story of critical care leadership in predominantly white schools - Williams, LaTisha (My University, 2025)
Many PK-12 school districts have expressed a desire to hire more culturally diverse leaders, yet the voice and representation of Black female leaders remain largely ignored. Despite a history of successful and transformative leadership, Black women continue to be underrepresented in educational literature, theory, and research. According to the National Center for Education Statistics, 77% of public-school leaders in 2020–2021 were white, and existing research overwhelmingly focuses on the leadership experiences of Black males, leaving the unique challenges and contributions of Black female Leaders largely unexplored. This study, informed by critical care theory, cultural boundary crossing, and Black feminist thought, employs a blend of narrative inquiry and autoethnography to examine the experiences of Black female leadership leading in predominantly white school settings. This research focuses on the leadership experiences of a Black female leader working with white students and families in a Midwestern town. The findings of this study reveal a relational model of educational leadership rooted in the lived experiences of a Black female leader and the white families and students engaged in the study. This working model of critical care leadership is organized around several key themes: maintaining high expectations, fostering personal connections and relationships, being present, practicing patience, providing resources, and supporting big decisions. These elements work together to create a culture of critical care and bridge building, allowing for authentic cultural boundary crossing between families, students, and Black female leadership.
Keywords: Leadership; Boundary crossing; Black female leadership; Critical care leadership; Black feminist thought; Bridge building; Third space; Autoethnography